Integrasi, Merger, Dan Konglomerasi : Implikasinya Terhadap Kebijakan Persaingan Usaha - Alifia Zahra Lathifah; Anida Amalia Rahma; Myalavina Ismathillah; Yasmin Intanalina; Naerul Edwin Kiky Aprianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Integration, merger, and conglomeration are increasingly common strategies implemented by companies in Indonesia to increase competitiveness in the increasingly tight global market. Corporate integration, both vertically and horizontally, is expected to create operational efficiency and expand market share, however, this process still faces challenges in terms of supervision of healthy business competition. Mergers as an instrument to strengthen market position in the financial sector and other industries also have the potential to reduce the level of market competition, which requires strict supervision by institutions such as the Business Competition Supervisory Commission (KPPU). Conglomeration, on the other hand, is a diversification strategy carried out by large companies to maintain financial stability, but also risks creating market dominance that is detrimental to small business actors. The findings in this article show that although this strategy provides efficiency benefits, strict regulation and fair supervision of business competition are needed to maintain market balance and support sustainable economic development. The implications of competition policy in Indonesia must continue to be adjusted to global dynamics and digitalization developments that affect integration and merger practices.